2021
DOI: 10.1093/jscr/rjab544
|View full text |Cite
|
Sign up to set email alerts
|

Systemic BCGosis following intra-renal instillation of BCG: a case report

Abstract: Bacillus Calmette-Guerin (BCG) immunotherapy is a mainstay of adjunctive therapy for non-muscle-invasive bladder cancer. The instillation of BCG in the upper urinary tract after complete tumour eradication has also been studied and used after kidney-sparing management. It is effective in increasing the length of remission. However, it is also associated with rare but severe local and systemic side effects which may potentially become life-threatening. We present a case report of a 37-year-old gentleman who dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other severe AEs have been described, such as (febrile) kidney tubercolosis [ 15, 32 ], ureteral stenosis requiring ileal substitution of the ureter [ 32 ] and bladder contraction [ 42 ]. In 2021, Schembri Higgans J et al [ 57 ] reported the first case of systemic BCGosis following intra-renal instillation that required long-term antituberculartreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Other severe AEs have been described, such as (febrile) kidney tubercolosis [ 15, 32 ], ureteral stenosis requiring ileal substitution of the ureter [ 32 ] and bladder contraction [ 42 ]. In 2021, Schembri Higgans J et al [ 57 ] reported the first case of systemic BCGosis following intra-renal instillation that required long-term antituberculartreatment.…”
Section: Resultsmentioning
confidence: 99%
“…Commonly observed adverse effects encompassed BCG-induced cystitis, bacterial infections, 14 increased urinary frequency, noticeable blood in the urine (frank hematuria), general discomfort (malaise), and fever. 15 , 16 Notably, a large cohort of 6753 patients, 1% developed BCG infections in the study period. 15 Another cohort of 418 patients, the incidence of severe complications was about 1.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Notably, a large cohort of 6753 patients, 1% developed BCG infections in the study period. 15 Another cohort of 418 patients, the incidence of severe complications was about 1.7%. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Steroids and anti TB therapy are frequently used in the treatment of BCGosis. 28,29 In individuals who have suspected BCGosis, it is critical to have a low threshold for initiating anti-TB therapy. 29 The majority of children with injection site problems and non-suppurative lymphadenitis responded completely within 6 months when treated conservatively.…”
Section: Treatmentmentioning
confidence: 99%